Safety and Efficacy of 188-Rhenium-Labeled Antibody to Melanin in Patients with Metastatic Melanoma - M. Klein; M. Lotem; T. Peretz; S. T. Zwas; S. Mizrachi; Y. Liberman; R. Chisin; J. Schachter; I. G. Ron; G. Iosilevsky; J. A. Kennedy; E. Revskaya; et al. (Journal of Skin Cancer)
There is a need for effective “broad spectrum” therapies for metastatic melanoma which would be suitable for all patients. The objectives of Phase Ia/Ib studies were to evaluate the safety, pharmacokinetics, dosimetry, and antitumor activity of 188Re-6D2, a 188-Rhenium-labeled antibody to melanin. Stage IIIC/IV metastatic melanoma (MM) patients who failed standard therapies were enrolled in both studies. In Phase Ia, 10 mCi 188Re-6D2 were given while unlabeled antibody preload was escalated. In Phase Ib, the dose of 188Re-6D2 was escalated to 54 mCi. SPECT/CT revealed 188Re-6D2 uptake in melanoma metastases. The mean effective half-life of 188Re-6D2 was 12.4 h. Transient HAMA was observed in 9 patients. Six patients met the RECIST criteria for stable disease at 6 weeks. Two patients had durable disease stabilization for 14 weeks and one for 22 weeks. Median overall survival was 13 months with no dose-limiting toxicities. The data demonstrate that 188Re-6D2 was well tolerated, localized in melanoma metastases, and had antitumor activity, thus warranting its further investigation in patients with metastatic melanoma.